History of Family: Denpasar’s 1950s generation in Cultural Transition - Wijaya, Nyoman; Lestari, Sri; Tuan, Nguyen Thanh (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: This study aims to find and discover the conditions that allow the 1950s generation in Pemecutan Kaja Village, North Denpasar District, Denpasar City, Bali-Indonesia, not to be involved in the tourism business sector, either in the middle or upper class. Newcomers mostly control the sector. Even though their place of residence is only 6 to 12 kilometers from the Sanur and Kuta tourist attractions. Why can this phenomenon happen? This question will be answered using a combination of family history and memory history methodology, while the data excavation (heuristic) stage uses Bourdieu's concepts of generative structural theory. The research results show that the defeat of local residents in the tourism business can be found in the factor of family management in carrying out their obligations as members of the Banjar. Many parents force or are forced to assign their sons to represent the family in carrying out customary obligations, so they must always stay home and work not far from home. Rarely are there those who dare to look for work in Sanur and Kuta, which are the main tourist destinations in Bali. Therefore, they do not have the basics of the tourism business. The unstoppable negative excesses of modernization have further narrowed the business opportunities in the tourism sector. This mental condition is influenced by their habitus, which is formed from the practice of fear and obedience to parents and the strong domination of the banjar. Abstrak: Studi ini bertujuan untuk mencari dan menemukan kondisi-kondisi yang memungkinkan generasi tahun 1950-an di Desa Pemecutan Kaja, Kecamatan Denpasar Utara, Kota Denpasar Bali-Indonesia tidak terlibat di sektor bisnis pariwisata, baik di kelas menengah maupun atas. Sektor tersebut kebanyakan dikuasai oleh para pendatang. Padahal tempat tinggal mereka berjarak hanya 6 hingga 12 kilometer dari objek wisata Sanur dan Kuta. Mengapa fenomena tersebut bisa terjadi? Persoalan itu akan dijawab dengan memakai perpaduan metodologi sejarah keluarga dan sejarah memori, sedangkan tahap penggalian data (heuristik) menggunakan konsep-konsep teori strukrural generatif Bourdieu. Hasil penelitian menunjukkan kekalahan penduduk lokal dalam bisnis kepariwisataan dapat dicari pada faktor manajemen keluarga dalam menjalani kewajiban sebagai anggota banjar. Banyak orang orang tua yang memaksa atau terpaksa menugaskan anak laki-lakinya mewakili keluarga dalam melaksanakan kewajiban adat, sehingga mereka harus selalu tinggal di rumah dan bekerja pun tidak jauh-jauh dari rumah. Jarang ada yang sampai berani mencari pekerjaaan ke Sanur dan Kuta, yang merupakan destinasi wisata utama di bali. Oleh karena itu mereka tidak memiliki dasar-dasar bisnis pariwisata. Ekses negatif modernisasi yang tidak terbendung semakin mempersempit peluang berbisnis di sektor pariwisata. Kondisi kejiwaan itu dipengaruhi oleh habitusnya yang terbentuk dari praktik rasa takut dan kepatuhan kepada orang tua dan dominasi banjar yang begitu kuat.